A Comparative Study of Multilevel and Conventional Inverters: Comparing Multilevel and Conventional Inverters in High Power Industrial Applications (Journal of Advances and Scholarly Researches in Allied Education, 2020)
From the past couple of decades, multilevel inverter technologies are suitable for high power industrial applications. Multilevel inverter synthesizes several DC sources. Multilevel inverter is the most suitable technology for conversion in renewable sources. This study which discussed about Multilevel Inverter Topologies, Topology Comparison, Simulation and Analysis, Multilevel inverter topology and a comparative study of Multilevel inverter topologies in terms of number of switches, harmonic content and efficiency. These topologies are cost effective as compare to conventional multilevel inverters. Despite of many advantages, multilevel inverter with reduced switches basis some advantages like the voltage stress on the individual switches increases. For that, it is recommended to use switches of high rated values. All the topologies are modelled using MatlabSimulink and the results are validated and compared.